Victimization, substance use, and sexual aggression in male adolescent sexual offenders - Marini, Victoria A. (Criminal justice and behavior, 2014)
Relations among childhood victimization, substance use prior to the commission of a sexual offense, and force used during a sexual offense were examined in a sample of residentially based, male juvenile sex offenders (n = 406; Mage = 16.6). Marshall and Marshall?s (2000) theory of sex offending proposes that childhood victimization, among other factors, creates a vulnerability to offend, which when paired with disinhibition (e.g., from substance use) may lead to sexual offending. Guided by this theory, we examined whether substance use prior to the commission of a sexual offense mediated the relation between trauma and force used in sexual offending. Six mediation analyses were used to examine subtypes of childhood victimization and the effects of cumulative victimization. Results provided support for partial mediation of substance use prior to a sexual offense on the effects of cumulative victimization on force used during a sexual offense. Theoretical and clinical implications are discussed.